Islamic Religious Education as a Foundational Basis for Adolescent Behavior in Central Lombok (PT. LARPA JAYA PUBLISHER, 2024)
This study explores the role of Islamic Religious Education (IRE) as a foundational basis for adolescent behavior in Central Lombok. Adolescence is a critical developmental stage where individuals begin to form moral values, identity, and behavior. Islamic Religious Education plays an essential role in guiding adolescents to develop ethical awareness, discipline, and responsibility according to Islamic principles. This descriptive study involved 65 adolescents in Central Lombok, with data collected through a Google Form questionnaire focusing on knowledge of Islamic teachings and behavioral practices. The findings describe adolescents’ understanding of Islamic education, daily religious practices, and moral conduct in social life. The study emphasizes that effective Islamic Religious Education delivered through schools, families, and community institutions can strengthen adolescents’ moral values, self-control, and social responsibility. Strengthening collaboration between educators, parents, and religious leaders is crucial in fostering adolescents who are morally grounded and capable of adapting to modern social and technological challenges.